KORELASI ANTARA DIAMETER DAN KERAPATAN TEGAKAN JATI UNGGUL NOMOR KLON 97 DAN 110 PADA UMUR 10 TAHUN DI KPH NGAWI, PERHUTANI JAWA TIMUR Correlation Between Diameter and Density of Superior Teak Standings Clones Number 97 and 110 At 10 Years of Age at KPH N - MUHAMMAD FADHIL AMIRUDDIN SUDOMO; Suryo Hardiwinoto; Sapto Indrioko Indrioko; Budiad Budiad (Agrienvi: Jurnal Ilmu Pertanian, 2018)
Teak clone number 97 and 110 have been developed by Perum Perhutani and Fakultas Kehutanan Universitas Gadjah Mada year 2004 / 2005. The aim of this research is to know survival rate, stand density, growth; and relation between level of stand density within growth of teak clone number 97 and 110 at the age of 10 years in BKPH Begal KPH Ngawi, Perum Perhutani East Java. Research is committed through making 32 checks measure permanent of the size 60 m x 50 m. The result of research indicated that after age 10 years, teak clone number 97 and 110 have survival rate 69,77 % or with stand density 581 trees/ha. There are 252 trees/ha experience death in range. Growth data indicate that there is relationship of negativity between growth of diameter with stand density, that is with value of correlation (r) = Ë— 0.6598. The relationship is explainable through y's regression equation= Ë—0.008x+25.46, with value RÂ² = 0.435.